REPRESENTAÇÕES SOCIAIS E SUA RELAÇÃO COM A QUALIDADE DE ÁGUA EM COMUNIDADES DO ENTORNO DO PARQUE ESTADUAL DO IBITIPOCA, MG-BRASIL - Galvão, Davi Fortes; Dupas, Francisco; Otênio, Marcelo (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2016)
The objective of this research was to raise the social representations (SR) watershed (BHs) for communities surrounding the Ibitipoca State Park, relating to the conservation status of water resources (WR) and agricultural practices. Quantitative technique was used of the collective subject discourse with taped interviews that retrieve opinions, representations, placements, traditional knowledge, beliefs and attitudes. Resulted in the lifting of the SR in relation to rivers and streams in relation with the quality of WR and use variables and soil cover. It was verified the existence of SR more and less impactful when compared with each other and that these SR affect the quality of WR according to the speeches, analysis and study of water use and soil cover. We conclude that depending on the SR of the individual, there is a greater tendency of subject in adopting practices that are more conservationists in the SR function assigned to the theme. The study of the use and soil cover showed how manifest themselves and how the SR influence on land use. Water analyses were instrumental in the relationship of the SR with its impact on WR communities.